Regulation of coronavirus gene expression by the 5'-untranslated region. - Guo, Huiling. (2010)
The regulatory properties of the 5’-untranslated region (5’-UTR) of the avian infectious bronchitis virus (IBV) were investigated through designing of plasmids which contained different mutations within the 5’-UTR: full-length (pUTR-wt), 362- nucleotides (nts) deleted (pUTR-362del) and stem-loop 1 (SL1) disrupted (pSL1- dsmut). By inserting a Firefly luciferase gene into the constructs, differences in gene expression were determined by expressing these plasmids in a mammalian cell system through transfection and measuring the expression levels through luciferase assays and immunoblotting. As a result of deleting 362 nts from the 5’-UTR, a 2-fold increment in gene expression was observed, which confirmed the finding made by Liu et al. (1998). Furthermore, it was found that a disruption of SL1 could result in a slight decrease in gene expression. Hence, these suggest that nts 363 to 528 in the 5’-UTR might be important in enhancing gene expression while SL1 could contribute itself as an initiator for gene expression in IBV.